Gymnastic wrist injuries - Gabel, G. T. (Clinics in Sports Medicine, 1998)
Wrist injuries in the gymnast are due to the transformation of the upper extremity into a weight bearing entity. Both acute and chronic disorders occur and are difficult to manage in these athletes because of the intensity of training and competition. Treatment is dependent on the injury as well as the expectations of the patient, coach, and family--a situation that at times may alter the usual management program.